Pengaruh Sport Massage Terhadap Kecepatan Tendangan Push Kick Pada Atlet Kickboxing Han Academy Kota Malang - Zheldy Armando Anggara; Agus Tomi; Usman Wahyudi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The research problem that the researchers took was that 15 Han Academy kickboxing athletes in Malang City often experienced tension in their leg muscles during training, so that when carrying out the training program the push kick kick speed was less than optimal. This study aims to find out whether sports massage has an effect on push kick kick speed for Han Academy kickboxing athletes, Malang City. The method used in this research is a pre- experimental research method using a one group pretest-posttest design. The subjects of this research were 15 participants, selected using total sampling. The instrument used is a test, the test uses a stopwatch to count the number of repetitions of push kick kick speed, when carrying out the test activities it is recorded and documentation is added. The tests carried out included pre-test, treatment, and post-test for the number of repetitions of push kick kick speed. Based on the results of data analysis, it shows that the paired T-test with a confidence level of 95% of the push kick kick speed shows that the sig. (2 tailed) of 0.000 is smaller than The results and discussion can be concluded that the relationship between sports massage and push kick kick speed is influential, with sports massage, tired muscles become flexible and relaxed again because of sports massage so that the push kick speed training of Han Academy kickboxing athletes increases.